Melatonin Improves Salt Tolerance in Tomato Seedlings by Enhancing Photosystem II Functionality and Calvin Cycle Activity - Xianjun Chen; Bi Chen; Yao Jiang; Jianwei Zhang; Mingjie Liu; Qin Yang; Huiying Liu (Plants, 2025)
Salt stress severely impairs photosynthesis and development in tomato seedlings. This study investigated the regulatory role of exogenous melatonin (MT) on photosynthetic performance under salt stress by determining chlorophyll content, chlorophyll a fluorescence parameters, Calvin cycle enzyme activities, and related gene expression. Results showed that salt stress significantly reduced chlorophyll content and impaired photosystem II (PSII) functionality, as evidenced by the increased minimum fluorescence (Fo) and decreased maximum quantum efficiency of PSII (Fv/Fm) and effective PSII quantum yield (ΦPSII). MT application mitigated these negative effects, as reflected by higher Fv/Fm, increased chlorophyll content, and lower non-photochemical quenching (NPQ). In addition, MT-treated plants exhibited improved PSII electron transport and more efficient use of absorbed light energy, as shown by elevated ΦPSII and qP values. These changes suggest improved PSII functional stability and reduced excess thermal energy dissipation. Furthermore, MT significantly enhanced both the activity and expression of key enzymes involved in the Calvin cycle, including ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), Rubisco activase (RCA), phosphoglycerate kinase (PGK), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), fructose-1,6-bisphosphatase (FBPase), fructose-bisphosphate aldolase (FBA), transketolase (TK), and sedoheptulose-1,7-bisphosphatase (SBPase), thereby promoting carbon fixation and ribulose-1,5-bisphosphate (RuBP) regeneration under salt stress. Conversely, inhibition of endogenous MT synthesis by p-CPA exacerbated salt stress damage, further confirming MT’s crucial role in salt tolerance. These findings demonstrate that exogenous MT enhances salt tolerance in tomato seedlings by simultaneously improving photosynthetic electron transport efficiency and upregulating the activity and gene expression of key Calvin cycle enzymes, thereby promoting the coordination between light reactions and carbon fixation processes. This study provides valuable insights into the comprehensive regulatory role of MT in maintaining photosynthetic performance under saline conditions.